2009
DOI: 10.1017/s1460396908006596
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the research agenda in Australian radiation therapy: the current picture

Abstract: In recent years the role of the radiation therapist (RT) has increasingly evolved. In Australia, one of the major developments has been the transition from practice which was rarely based on scientific evidence, to the profession today which engages in and incorporates research into everyday practice. The aim of this article is to provide an insight into the current status of Australian radiation therapy research. In order to present a national overview, a survey relating to research activity was e-mailed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 7 publications
3
32
0
Order By: Relevance
“…Numbers undergoing Post Graduate (PG) training is encouraging with 43 staff qualified to Masters level and a further 58 in progress with Masters level study; comparable with PG qualifications reported by Wright et al (12). Unfortunately the upward trend in higher degree doctoral qualifications in Australia(12) was not apparent yet in this UK survey with only 1 doctoral trained Therapeutic Radiographer identified from responding centres; this is an area where Therapeutic Radiographers need to increase their aspirations.…”
Section: Support and Trainingsupporting
confidence: 65%
See 3 more Smart Citations
“…Numbers undergoing Post Graduate (PG) training is encouraging with 43 staff qualified to Masters level and a further 58 in progress with Masters level study; comparable with PG qualifications reported by Wright et al (12). Unfortunately the upward trend in higher degree doctoral qualifications in Australia(12) was not apparent yet in this UK survey with only 1 doctoral trained Therapeutic Radiographer identified from responding centres; this is an area where Therapeutic Radiographers need to increase their aspirations.…”
Section: Support and Trainingsupporting
confidence: 65%
“…A third of centres had no radiographer who led on research activity and this will substantially limit the development of a research culture. A total of 40.3 WTE RR posts were reported with 4 centres recording 4 RRs in post; a substantial improvement to the total WTE post holders reported by wright et al (12).…”
Section: Leadership and Culturementioning
confidence: 69%
See 2 more Smart Citations
“…Research roles and qualifications are not embedded in the clinical setting across health disciplines . However, increased number of MRS professionals with doctoral qualifications as well as research training and mentorship in the whole profession will add to the evidence base for practice …”
Section: Introductionmentioning
confidence: 99%